Digital Twin: A Future Health Challenge in Prevention, Early Diagnosis and Personalisation of Medical Care in Paediatrics - Calcaterra, Valeria; Pagani, Valter; Zuccotti, Gianvincenzo (International journal of environmental research and public health, 2023)
In childhood asthma, likewise, where different determinants of asthma symptoms need to be considered, including the treatment and the environment (pollutants, allergens, weather), DTS could be used to define the appropriate treatment in real time and/or to adopt the appropriate mitigation measures in subjects at high risk of asthma, and to determine an optimal medication dose and treatment plan, leading to a decrease in both the costs and the difficulties involved in clinically managing the disease [1,8]. Through health technology, history, demographics, lifestyle data over time of an individual physical marker, and vital signs collected by health bracelets and watches, instrumental data and several biomarkers may be collected and used to train artificial intelligence within the scope of predicting health risks using a mathematical model [11]. A DTS in the health system offers a virtual disease representation, offering the possibility to test scientific hypotheses and predict the interaction of pathogenic components and their effect on children and adolescents [11]. The complexity and costs of DTS will be comparable to those of projects such as the Human Genome Project; in addition, DTS may lead to an improvement in health and access to healthcare, performing early diagnosis of diseases, performing personalized treatment, and offering innovative research directions [3,12,13].